The protective role of mindful parenting against child maltreatment and aggressive behavior: an exploratory study among Chinese parent-adolescent dyads - Lei Yue; Naixue Cui; Nadya Golfenshtein; Naisong Cui; Yinjun Hao; Pingping Lyu (BMC, 2022)
Abstract Background It is well-established that child maltreatment practiced by parents is associated with adolescent aggression. Emerging evidence has suggested that higher levels of mindful parenting are associated with fewer negative parenting practices. However, the relationships among mindful parenting, child maltreatment, and adolescent aggression remain unclear. Aim To examine the association between mindful parenting, child maltreatment, and adolescent aggressive behavior among Chinese parent-adolescent dyads. Methods Survey data from 554 Chinese parent-adolescent dyads were used for the analysis. Parents reported mindful parenting, and adolescents reported three forms of child maltreatment (i.e., physical abuse, psychological aggression, and neglect) by their parents and aggressive behavior. Path models were used to analyze whether higher levels of mindful parenting were associated with decreased likelihood of parent-to-adolescent maltreatment that were further related to lower levels of adolescent aggression. Results Mindful parenting and its two factors (i.e., interaction with full attention and compassion and acceptance) were associated with lower likelihood of physical abuse and psychological aggression, which were related to decreased levels of adolescent aggressive behavior. Stratified analyses by parent gender showed that the path from interaction with full attention to adolescent aggression through psychological aggression was also significant or marginally significant in both mother-adolescent and father-adolescent dyads. Stratified analyses by adolescent gender demonstrated that the paths from interaction with full attention to physical abuse and psychological aggression were significant, which were also significantly correlated with adolescent aggression among male adolescents, whereas the mindful parenting-child maltreatment-adolescent aggression paths were not significant among female adolescents. Conclusions The findings contributed to the existing literature by assessing mindful parenting as a multifaceted construct and exploring the gender differences in the relationships. Gender-tailored interventions to improve mindful parenting, specifically focusing on the parents' ability of interacting with adolescents providing full attention, compassion, and acceptance may work towards preventing child maltreatment and promoting adolescent behavioral health.